MEDIPIA Berbasis Virtual Reality untuk Meningkatkan Literasi Lingkungan Siswa pada Topik Pencemaran Air - Adzan Akhmad Nazari; Afrizal Mayub; Henny Johan (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to improve students’ environmental literacy by developing MEDIPIA, an interactive science learning media based on Virtual Reality (VR). The focus of the research is on water pollution at Teluk Sepang Beach, a coastal area affected by thermal waste discharge from the Teluk Sepang Power Plant. The study follows the 4D development model, which consists of Define, Design, Develop, and Disseminate stages, integrating both media development and environmental analysis. A field trial involving 30 seventh-grade students from SMPN 52 Bengkulu Utara was conducted using a one-group pretest-posttest design to assess changes in students’ environmental literacy. At the same time, seawater quality was analyzed at seven observation points using five parameters: temperature, pH, salinity, dissolved oxygen, and turbidity, based on standards from the Ministry of Environment Decree No. 51 of 2004. The findings indicate ecological disturbance near the wastewater discharge outlet, characterized by temperatures above 30°C, decreased pH at two points, salinity levels below 33‰, turbidity exceeding 5 NTU at four points, and dissolved oxygen above 5 mg/L. Expert validation rated MEDIPIA as highly suitable for educational use, with an average score of 91.79%. Statistically, student environmental literacy increased significantly after using MEDIPIA, with an N-gain score of 0.7 and a p-value of 0.001 (p < 0.05). These results suggest that VR-based interactive media can bridge scientific environmental data and student learning, contributing to the development of context-based science education that addresses local environmental issues